NARRATIVE REVIEW OF PSYCHOSOCIAL RISK FACTORS ASSOCIATED WITH MENTAL ILLNESS IN HEALTHCARE WORKERS - Rodrigues, Fernanda Cristina Teixeira; Ferreira, André Costa; dos Santos, Ricardo Marciano; Carlos, Aluana Santana; Moreno, Adalgiza Mafra; Mendes, Paulo Roberto Moreira; Soares, Paula Fernanda Chaves; Gusmão, Tatiane Daniele de Almeida Costa (Seven Editora, 2025)
Healthcare workers are exposed to a range of psychosocial risks arising from intense work conditions, high emotional demands, and adverse organizational environments, which make them vulnerable to mental health problems such as stress, anxiety, depression, and burnout. The aim of this study is to analyze the psychosocial factors associated with mental illness among these professionals and discuss how the findings can support occupational health surveillance strategies. This review is based on recent national and international studies (2019–2025) that demonstrate a strong association between psychosocial risks, workload, and psychological distress across different healthcare settings. Evidence also indicates that the COVID-19 pandemic further intensified these risks. This article synthesizes the current evidence and outlines directions for promoting mental health in the workplace. DOI: https://doi.org/10.56238/sevened2025.029-124